Social Media Instagram, Tiktok, dan X Dalam Pengungkapan Pelanggaran Hukum Dalam Konflik Antara Palestina Dan Israel - Andy Satria; M.Taufiq Kurniawan; Putri Imilia Amanda; Daniyal Arkan (Jurnal Teknik Informatika dan Teknologi Informasi, 2024)
This research explores the role of social media (Instagram, TikTok, and Platform X) in exposing legal violations during the Palestine-Israel conflict. The study aims to understand the impact of these three platforms through the Instagram account @suarasurabayamedia. The findings indicate that Instagram accelerates information dissemination and visual impact, TikTok creates mass awareness through short video formats, and Platform X provides space for diverse perspectives. The social media's focus on Israeli atrocities influences public opinion, supports international solidarity movements, and triggers international pressure and UN resolutions. The impact of social media involves information dissemination, support, amplification of marginalized voices, but also carries the risk of inaccurate information and criticism from authorities. Therefore, the use of social media needs to be balanced with responsibility to prevent the spread of harmful information or worsening conflict situations.